Triple-Clad Fiber Combiner for Holmium-Doped Fiber Lasers Clad-Pumping - Nicolas Dalloz; Stefano Bigotta; Thierry Ibach; Christophe Louot; Thierry Robin; Anne Hildenbrand-Dhollande (Photonics)
The development of a high-power 7 × 1 triple-clad fiber combiner aimed at resonantly clad-pump holmium-doped fiber lasers is presented. Thanks to the implementation in the combiner of a low refractive index glass capillary, we show that the developed combiner is compatible with power scaling. Due to the hexagonal arrangement of its seven single-mode input fibers, the presented combiner can also be used in a 6 + 1 × 1 configuration. This characteristic of the fiber component allows for holmium-doped fiber lasers to be studied and developed with both single-oscillator and master-oscillator power amplifier architectures.